Colonialism and Apartheid Against Fragmented Palestinians: Putting the Pieces Back Together. (1st April 2016) - Rinad Abdulla
Abstract : Current dominant legal and political discourse narrows the destruction of Palestinian indigenous society in a historical homeland to the Israeli military occupation of the West Bank and Gaza. This erroneously assumes that an end to Israel's occupation would effectively end hostilities. Israel has used deliberate demographic engineering in the entire Palestine–Israel region to fragment territory and people to create and maintain dominance of an immigrant Jewish population: demographically, economically and politically. Palestinians are segregated and governed by some form of apartheid and colonialism depending on their location. This article challenges the narrow discourse and examines the Palestine–Israel situation within the context of settler colonialism, apartheid and state-sponsored systematic discrimination. From this perspective, the only sustainable and comprehensive solution is to challenge the validity of the Israeli state based on decolonization, just as apartheid in South Africa was challenged. Decolonization opens up the possibility of reversing fragmentation and restoring territorial integrity and sovereignty to the people of Palestine based on a democratic polity with equal rights for all its inhabitants.